Modelling of ship engine exhaust emissions in ports and extensive coastal waters based on terrestrial AIS data – An Australian case study. (January 2015) - Goldsworthy, Laurie; Goldsworthy, Brett
Abstract: A model is developed to calculate and spatially allocate ship engine exhaust emissions in ports and extensive coastal waters using terrestrial Automatic Identification System data for ship movements and operating modes. The model is applied to the Australian region. The large geographical extent and number of included ports and vessels, and anomalies in the AIS data are challenging. Particular attention is paid to filtering of the movement data to remove anomalies and assign correct operating modes. Data gaps are filled by interpolation and extrapolation. Emissions and fuel consumption are calculated for each individual vessel at frequent intervals and categorised by ship type, ship size, operating mode and machinery type. Comparisons of calculated port emissions with conventional inventories and ship visit data are favourable. Estimations of ship emissions from regions within a 300 km radius of major capital cities suggest that a non-negligible percentage of air pollutants may come from ships. Highlights: Model for estimating regional and in-port ship engine exhaust emissions. Ship movement data from Automatic Identification System. Movement data filtered for anomalies, interpolated and extrapolated. Emissions data categorised and spatially allocated. Comparisons with emissions from non-ship sources.